Who's covering who in the postmodern 90s? Subverting the orientalist image in the contemporary North African Francophone text - Orlando, V (Purdue Research Fdn, 1997)
[Abstract Not Available]
8th Annual Purdue University Conference on Romance Languages, Literatures, and Film -- 1996 -- PURDUE UNIV, W LAFAYETTE, IN